STRATEGI TATA KELOLA PEMBIAYAAN PENDIDIKAN USAI EFISIENSI ANGGARAN: Systematic Literature Review - restarie, maya diaz; Ahmad, Masduki; Rochimah, Heni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of budget efficiency in education through government policies such as Presidential Instruction No. 1 of 2025 has raised various concerns regarding its impact on the quality of education. This article aims to examine strategies for managing educational financing in the face of budget efficiency using a systematic literature review approach. Data were collected from relevant literature on education financing and budgeting. The findings reveal that effective governance of educational financing must uphold the principles of transparency, accountability, effectiveness, and efficiency. Proper financial governance not only ensures optimal budget utilization but also prevents fund misuse and enhances the quality of educational services. In the context of budget efficiency, financial management strategies should focus on optimizing operational costs, improving infrastructure, and empowering human resources to remain aligned with national education development goals and the Vision of Advanced Indonesia 2045. Strengthening governance requires synergy between regulations, financial management, and collaboration among stakeholders.